PROBABILISTIC EVALUATION OF LIQUEFACTION-INDUCED GROUND FAILURES TRIGGERED BY SEISMIC LOADING IN URBAN ENVIRONMENT; CASE STUDIES FROM GREECE - Papathanassiou, G.; Pavlides, S. (Bulletin of the Geological Society of Greece, 2010)
An issue that should be taken into account by urban planners in Greece, for the extension of urban areas, is the likelihood of earthquake-induced ground deformations. In this paper, information is provided regarding the methodology that is applied for the prediction of liquefaction manifestations in urban environment. In particular, a review of our research concerning the evaluation of the probability of liquefaction-induced ground disruption in three towns, Larissa, Edessa and Lefkada, is presented. The evaluation of probability was achieved using the Liquefaction Potential Index methodology and the relatively classification, introduced in late 80’s and modified by Papathanassiou (2008).